Áreas de reproducción de peces migratorios en la cuenca alta del río Magdalena, Colombia (2014)
During the 2011-2012 hydrological cycle, weekly samples were taken to evaluate the reproduction of migratory fishes in the area of influence of the El Quimbo hydroelectric project. This analysis considered the abundance and density of individuals in each of the samples taken in the Magdalena, Páez and Suaza rivers near Gigante and Garzón (Huila). Twenty taxa were captured. Four were confirmed taxonomically (Prochilodus magdalenae, Pseudopimelodus spp, Astyanax fasciatus and Pimelodus spp), the remaining 16 were classified according to the descriptions of different morphotypes present in the key used. Astyanax fasciatus and Pimelodus spp were the most frequent and abundant.